THE MODEL OF FOSTERING THE CIVIL SELF-DETERMINATION OF HIGH SCHOOL STUDENTS - O. T. Koveshnikova (Образование и наука)
The paper considers the model construction basics of developing the civil self-determination of the high school students in the context of holistic and axiological approaches; the definition of the above aspect of self-determination being given, its stages identified. The author comes up with the idea of creating the pedagogical situations of the  civil dialog along with the universal didactic means for all educational stages including the heuristic tasks, discussions and situational role play; the content and componentcomposition of the civil dialog being introduced including such varieties as the dialog of a teacher and student, students' interaction, and inner dialog.The formation of the civil self-determination is regarded by the author as the personality development aimed at creating, realizing and accepting the ideal of a citizen. In authors' opinion, the above process is conditioned by interactions of objective values and subjective personal conceptions of values, and results in acknowledging and adoption of the fatherland and civil society values.